Medication Administration Through Feeding Tubes in a Tertiary Hospital: A Retrospective Observational Study - Zhu Y; Zhu B; Jin P (Risk Management and Healthcare Policy)
Yuanchao Zhu, Bolin Zhu, Pengfei Jin Department of Pharmacy, Beijing Hospital, National Center of Gerontology, Institute of Geriatric Medicine, Chinese Academy of Medical Sciences, Beijing Key Laboratory of Assessment of Clinical Drugs Risk and Individual Application(Beijing Hospital), Beijing, 100730, People’s Republic of ChinaCorrespondence: Pengfei Jin, Email j790101@163.comAim: This study aimed to investigate the prevalence and types of errors associated with oral medication administration via feeding tubes (FTs) in a tertiary hospital in Beijing.Methods: A retrospective observational study was conducted at Beijing Hospital between January 2018 and December 2022. All inpatients aged of 18 and above who received at least one oral medication via FTs were included. Medical records were meticulously collected and analyzed.Results: A total of 7,243 patients were identified as part of the tube feeding group, representing a prevalence rate of 6.26% among hospitalized patients receiving oral medication. Compared to the general hospitalized population, patients in the tube feeding group exhibited a higher proportion of male patients (59.74% vs 48.91%), older age [(68.00± 14.99) vs (59.75± 16.38)], lower weight [(65.75± 13.32) vs (67.82± 12.72)], increased rates of being bedridden (18.06% vs 5.38%), longer hospital stay [(21.56± 28.12) vs (8.88± 10.38)], and a greater number of prescribed medication types [(51.21± 19.37) vs (23.35± 15.04)]. On average, patients in the tube feeding group were administered 8.92± 6.78 types of oral medications. A significant percentage of patients in the tube feeding group experienced inappropriate medication administration, reaching 65.43%. Among these cases, the rate of inappropriate medication administration for patients receiving nasogastric tube and nasojejunal tube were 64.06% (4186/6535) and 78.11% (553/708), respectively. In total, there were 10,164 instances of inappropriate medication administration, averaging 1.40 times per patient in the tube feeding group. Inappropriate medications included enteric-coated drugs, modified-released, soft capsules, and other non-crushable drugs.Conclusion: Our results Our findings highlight a significant issue of inappropriate medication administration via FTs. Ensuring the accurate administration of orally prescribed medications to patients with FTs is a complex task that requires immediate attention.Keywords: tube feeding, inappropriate medication, medication errors, nasogastric tube, nasojejunal tube